The Investigation of Relationship Between Procrastination and Discomfort Intolerance in University Students. - Levent Sutcigil; Asiye Nur Nihan Yurdakul; M.Hakan Turkcapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
In this study, it is aimed to compare the strengths of people with high and low procrastination tendencies towards discomfort intolerance and to examine the relation between procrastination behavior and discomfort intolerance. The working group constitutes 70 university students who are staying in Istanbul and accepting voluntary participation. In this research; The General Procrastination Scale" and "Academic Procrastination Scale", "Resilience Scale", Discomfort Intolerance Scale and "Personal Information Form" were used. Findings have been studied with SPSS (Social Sciences Statistical Package for Science) program. In this study, the relationship between general procrastination, academic procrastination, distress and discomfort intolerance with each others were analyzed. It was found that there was a positive relationship between distress intolerance and academic average, a positive relationship between general delay and academic delay, and an inverse relationship between general delay and academic average. According to the findings, general procrastination, discomfort, and distress were not found. Same way, There is no significant relationship between academic procrastination) and discomfort intolerance and distress. Key words: procrastination, distress tolerance, discomfort tolerance [JCBPR 2017; 6(3.000): 123-132]